Globalization and Deindustrialization: The Political Economy of Domestic Institutions (or Lack Thereof) in the Post-New Order Indonesia - Rakhmat Syarip (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Unair, 2017)
This paper discusses determining factors behind Indonesia’s deindustrialization in the post-New Order era. Over time, manufacturing sector shows decreasing contribution to Indonesia’s GDP, while industrial transformation stagnates with limited high-technology exports. Using Linda Weiss’ (1998) Governed Interdependence and Christopher Dent’s (2003) Adaptive Partnership theories, this paper offers political-economy arguments to explain the phenomenon. Internationally speaking, while it is true that neoliberal globalization imposes some restrictions, it is too much to claim the death of industrial policy. Rather, it is the limitation of domestic institutions that is best explained Indonesia’s case. Using automotive, rattan and copper industries as case studies, the argument consists of two parts. First, in post-New Order Indonesia there is insufficient coordination between state and capital (both foreign and domestic). Second, the state in Indonesia lacks sufficient administrative capacity. The paper recommends Indonesia to invest in domestic institution as a means to reindustrialize.